Removal of manganese ion using integral membrane incorporated with rice husk ash / Norin Zamiah Kassim Shaari, Nabilah Huda Alias, Nurul Ati - Kassim Shaari, Norin Zamiah; Alias, Nabilah Huda; Ati, Nurul (Universiti Teknologi MARA Shah Alam, 2023)
Wastewater treatment is a method of ensuring that the water supply is clean and free from contaminants. Manganese is a pollutant that needs to be removed from the water as it is harmful and usually triggers concern about water quality and water distribution system issues. Besides the adsorption method, membrane technology is efficient due to its mild and environmentally friendly process. This research focused on the production of integral membranes from a blend of polyvinyl alcohol/chitosan/polysulfone/ polyethylene glycol cross-linked with silica extracted from rice husk ash (RHA) by using the phase inversion method. The silica was incorporated into the membrane formulation through a sol-gel reaction. The goal of this research was to determine the potential utilization of silica from RHA in the membrane’s formulation to remove manganese ions from various concentrations of manganese solutions. The loadings of RHA were varied at 2, 3 and 5 % wt./wt. polymer. The formulated membranes were then characterized in terms of thermal stability by Thermogravimetric analysis, functional group by Fourier Transform Infrared Spectroscopy, and surface morphology by Scanning Electron Microscopy. The performances of the membranes were tested through filtration of manganese ions solutions and antifouling analysis. The results showed that all membranes including membranes from the polymer blend were able to remove more than 94 % manganese ions. However, the membrane incorporated with 2 % RHA portrayed the best performance in terms of obtaining the highest flux for both water and manganese as feed solution respectively, which also resulted in the highest relative flux recovery ratio at 62.50 % from the antifouling analysis. These findings have proven the successful incorporation of RHA in the form of silica powder, which shows the potential utilization of RHA in membrane fabrication.